Water and salt balance in young male football players in training during the holy month of Ramadan - Shirreffs, S. M.; Maughan, R. J. (Journal of Sports Sciences, 2008)
The aim of this study was to assess water and salt balance in young football players in training during Ramadan. Measurements were made in 92 young male football players before and during the month of Ramadan. Fifty-five participants were observing Ramadan fasting, while the other 37 participants were eating and drinking without restriction. In week 3 of Ramadan, water and salt balance measures were made during a training session of 60-70 min duration that was performed at an ambient temperature of 25-28°C and relative humidity of 50-53%. Body mass was recorded before and after training. Fluid intake was assessed in non-fasting players by weighing drink bottles before and after training, and the volume of any urine output was recorded. Sweat composition was estimated from absorbent patches applied to four skin sites for the duration of training. Mean sweat loss of players amounted to 1.41 litres (s = 0.36) in fasting players and 1.61 litres (s = 0.51) in non-fasting players (P = 0.038). Mean fluid intake during training in non-fasting players was 1.92 litres (s = 0.66). Sweat sodium concentration was 20 mmol/l (s = 8) in fasting players and 17 mmol/l (s = 7) in non-fasting players, and total sweat sodium loss during training was 0.67 g (s = 0.41) and 0.65 g (s = 0.37) [corresponding to a salt loss of 1.7 g (s = 1.1) and 1.7 g (s = 0.9)] respectively, with no difference between fasting and non-fasting players. Sweat sodium loss was not related to estimated dietary sodium intake (r = -0.07). These descriptive data show large individual variations in all measured parameters with relatively little difference in sweat parameters between fasting and non-fasting individuals.